Anti-skid process for EPE pearl wool

By adding ceramic particles to EPE pearl cotton and pressing anti-slip convex points on the surface, the problem of pearl cotton sliding during transportation is solved, the friction coefficient and anti-slip performance of pearl cotton is improved, and the stability and safety of transportation are ensured.

CN119502394APending Publication Date: 2025-02-25YANG ZHOU CITY FEIJIE TRAVEL ARTICLE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411706517.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Common pearl cotton is easy to slide due to the low surface friction coefficient during transportation, which affects the stability and safety of transportation.

Method used

By adding ceramic particles to the EPE pearl cotton production raw materials and pressing the anti-slip convex points on the surface of the pearl cotton using an embossing machine mold to form anti-slip convex points, the friction coefficient and anti-slip performance of the pearl cotton are improved.

Benefits of technology

It improves the friction coefficient and anti-slip performance of the pearl cotton surface, and enhances the stability and safety of the product during transportation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119502394A_ABST
    Figure CN119502394A_ABST
Patent Text Reader

Abstract

The invention discloses an EPE pearl wool anti-skid process, and relates to the field of pearl wool production, and the EPE pearl wool anti-skid process comprises the following steps: S1, weighing raw materials according to parts by weight; s2, adding the raw materials in the step S1 into a stirrer, and fully mixing and drying the raw materials, S3, adding the mixed raw materials into an extruder, heating and melting the raw materials, and adding ceramic particles into the extruder, and S4, injecting a foaming agent into the extruder, so that the raw materials are subjected to a foaming reaction, and the ceramic particles are added into the extruder. S5, extruding, cooling and forming the raw materials; and S6, pressing the surface of the pearl wool material by using an embossing machine mold to form the anti-skid salient points. By adding equal proportion of ceramic particles, the ceramic particles are distributed on the surface of the pearl wool, and the antiskid salient points are pressed on the surface of the pearl wool material, so that the friction coefficient of the surface of the pearl wool is increased, and the antiskid performance of the pearl wool is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of pearl cotton production, in particular to an EPE pearl cotton anti-slip process. Background Art

[0002] Pearl cotton is a soft foam material made of polyethylene foam. It has the characteristics of lightness, softness, sound insulation, shockproof and heat preservation. It is widely used in packaging, heat preservation and sound insulation fields.

[0003] When common pearl cotton is packaged, the product is protected during transportation by covering the outside of the product with pearl cotton. The product contacts the placement position through the surface of the pearl cotton. However, due to the low friction coefficient of the pearl cotton surface, its anti-slip performance is reduced. When the product shakes during transportation, the product is prone to sliding, which reduces the stability of the product and affects the safety of product transportation. Summary of the invention

[0004] The object of the present invention is to provide an EPE pearl cotton anti-slip process to solve the problems raised in the above background technology.

[0005] To achieve the above object, the present invention provides the following technical solution: an EPE pearl cotton anti-slip process, comprising the following steps: Step S1: weighing raw materials by weight, 95-120 parts of high molecular weight polyethylene raw materials, 1.1-1.8 parts of talc, 18-25 parts of monoglyceride, 0.3-0.5 parts of antistatic agent, 0.3-0.5 parts of foaming agent, 0.1-0.2 parts of anti-shrinkage agent, 0.1-0.2 parts of silica aerogel, 0.2-0.3 parts of flame retardant and 2.1-5.5 parts of ceramic particles; Step S2: the high molecular weight polyethylene raw material, talcum powder, monoglyceride, antistatic agent, anti-shrinkage agent, silica aerogel and flame retardant in step S1 are put into a mixer, and then fully mixed and dried; Step S3: adding the mixed raw materials into an extruder, heating and melting the raw materials, and adding ceramic particles into the extruder, and fully mixing the ceramic particles with the molten materials; Step S4: injecting a foaming agent into the extruder to cause the raw material to undergo a foaming reaction, thereby obtaining an EPE foam material, which is then transported as the extruder operates; Step S5: The melt-mixed material is transported to the head and die position of the extruder, the molten raw material is extruded, and the raw material is cooled and formed to prepare pearl cotton; Step S6: The extruded EPE is collected by a reeling device, and the EPE material is driven to move to the embossing machine position, and the embossing machine mold is used to press the surface of the EPE material to form anti-slip convex points.

[0006] Preferably, the foaming agent is made of azodicarbonamide material, the antistatic agent is one of sulfuric acid derivatives, phosphoric acid derivatives, amines, quaternary ammonium salts, imidazoles and ethylene oxide derivatives, and the anti-shrinkage agent is a low molecular weight polymer.

[0007] Preferably, the flame retardant is one of a bromine flame retardant, a phosphorus flame retardant and a nitrogen flame retardant, and the ceramic particles are one of alumina, a silicate and a carbonate.

[0008] Preferably, the stirring time of the raw materials in step S2 is 0.5-1h, the stirring temperature is 40-60°C, and the heating temperature of the extruder in step S3 is 180-230°C.

[0009] Preferably, the foaming agent injection pressure in the extruder in step S4 is 0-15 MPa, the hot pressing temperature of the embossing machine in step S6 is 80-100° C., and the hot pressing time is 5-8 s.

[0010] Preferably, in the step S4, during the heating process, butane in the butane gas tank is injected into the extruder using a butane gas pump, so that the liquid mixture is foamed into a microporous structure raw material using the effect of butane.

[0011] Preferably, in step S2, an antistatic agent is added to reduce the surface resistance of the pearl cotton material from 1014-10160 to 108-1010Q, and the antistatic coefficient of the pearl cotton is 109-10110.

[0012] Preferably, in step S5, the cooling and shaping treatment is carried out by cold air equipment, and then the shaped material is pre-pressed by flattening equipment. After the pre-pressing treatment, the flattening equipment is used for flattening again, and then the flattened and shaped material is wound up by a winding machine to obtain the EPE pearl cotton coil.

[0013] Preferably, the silica aerogel in step S1 is obtained by grinding aerogel blocks. The silica aerogel has a large specific surface area and a high porosity, and is used to thicken, thixotropically and reinforce the molten raw materials.

[0014] Technical effects and advantages of the present invention: (1) The present invention adds an equal proportion of ceramic particles to the raw materials for producing EPE pearl cotton. After the raw materials are heated and melted, the ceramic particles are mixed with the raw materials in a molten state, and the ceramic particles and the raw materials are evenly distributed. After the pearl cotton is cooled and shaped, the ceramic particles are distributed on the surface of the pearl cotton, thereby increasing the friction coefficient of the pearl cotton surface and ensuring the anti-slip protection ability of the pearl cotton; (2) The present invention uses an embossing machine mold to press the surface of the pearl cotton material to form anti-skid convex points, and the anti-skid convex points are evenly distributed on the surface of the pearl cotton, thereby increasing the friction resistance of the pearl cotton surface and improving the anti-skid performance of the pearl cotton. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 It is a schematic diagram of the anti-skid process of EPE pearl cotton of the present invention. DETAILED DESCRIPTION

[0016] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0017] The present invention provides Figure 1 The EPE pearl cotton anti-slip process shown includes the following steps: Step S1: weighing raw materials by weight, 95-120 parts of high molecular weight polyethylene raw materials, 1.1-1.8 parts of talc, 18-25 parts of monoglyceride, 0.3-0.5 parts of antistatic agent, 0.3-0.5 parts of foaming agent, 0.1-0.2 parts of anti-shrinkage agent, 0.1-0.2 parts of silica aerogel, 0.2-0.3 parts of flame retardant and 2.1-5.5 parts of ceramic particles; Step S2: the high molecular weight polyethylene raw material, talcum powder, monoglyceride, antistatic agent, anti-shrinkage agent, silica aerogel and flame retardant in step S1 are put into a mixer, and then fully mixed and dried; Step S3: adding the mixed raw materials into an extruder, heating and melting the raw materials, and adding ceramic particles into the extruder, and fully mixing the ceramic particles with the molten materials; Step S4: injecting a foaming agent into the extruder to cause the raw material to undergo a foaming reaction, thereby obtaining an EPE foam material, which is then transported as the extruder operates; Step S5: The melt-mixed material is transported to the head and die position of the extruder, the molten raw material is extruded, and the raw material is cooled and formed to prepare pearl cotton; Step S6: The extruded EPE is collected by a reeling device, and the EPE material is driven to move to the embossing machine position, and the embossing machine mold is used to press the surface of the EPE material to form anti-slip convex points.

[0018] The foaming agent is made of azodicarbonamide material, the antistatic agent is one of sulfuric acid derivatives, phosphoric acid derivatives, amines, quaternary ammonium salts, imidazoles and ethylene oxide derivatives, and the anti-shrinkage agent is a low molecular weight polymer.

[0019] The flame retardant is one of a bromine flame retardant, a phosphorus flame retardant and a nitrogen flame retardant, and the ceramic particles are one of alumina, silicate and carbonate.

[0020] The stirring time of the raw materials in step S2 is 0.5-1h, the stirring temperature is 40-60°C, and the heating temperature of the extruder in step S3 is 180-230°C.

[0021] In step S4, the foaming agent injection pressure in the extruder is 0-15Mpa, and in step S6, the hot pressing temperature of the embossing machine is 80-100°C, and the hot pressing time is 5-8s.

[0022] In step S4, during the heating process, butane in the butane gas tank is injected into the extruder using a butane gas pump, so that the liquid mixture is foamed into a microporous structure raw material using the effect of butane.

[0023] In step S2, an antistatic agent is added to reduce the surface resistance of the pearl cotton material from 1014-10160 to 108-1010Q, and the antistatic coefficient of the pearl cotton is 109-10110.

[0024] In step S5, the cold air equipment is used to cool and shape the material, and then the shaped material is pre-pressed by the flattening equipment. After the pre-pressing treatment, the flattening equipment is used to flatten the material again, and then the flattened and shaped material is wound up by the winding machine to obtain the EPE pearl cotton roll.

[0025] The silica aerogel in step S1 is obtained by grinding aerogel blocks. The silica aerogel has a large specific surface area and a high porosity, and is used to thicken, thixotropically and reinforce the molten raw materials.

[0026] Embodiment 1 Step S1: weighing raw materials by weight, 105 parts of high molecular weight polyethylene raw material, 1.5 parts of talc, 25 parts of monoglyceride, 0.3 parts of antistatic agent, 0.5 parts of foaming agent, 0.2 parts of anti-shrinkage agent, 0.1 parts of silica aerogel and 0.25 parts of flame retardant; Step S2: the high molecular weight polyethylene raw material, talcum powder, monoglyceride, antistatic agent, anti-shrinkage agent, silica aerogel and flame retardant in step S1 are put into a mixer, and then fully mixed and dried; Step S3: adding the mixed raw materials into an extruder, and heating and melting the raw materials; Step S4: injecting a foaming agent into the extruder to cause the raw material to undergo a foaming reaction, thereby obtaining an EPE foam material, which is then transported as the extruder operates; Step S5: The melt-mixed material is transported to the head and die position of the extruder, the molten raw material is extruded, and the raw material is cooled and formed to prepare pearl cotton; Step S6: The extruded EPE is collected by a reeling device, and the EPE material is driven to move to the embossing machine position, and the embossing machine mold is used to press the surface of the EPE material to form anti-slip convex points.

[0027] Embodiment 2 Step S1: weighing raw materials by weight, 105 parts of high molecular weight polyethylene raw material, 1.5 parts of talc, 25 parts of monoglyceride, 0.3 parts of antistatic agent, 0.5 parts of foaming agent, 0.2 parts of anti-shrinkage agent, 0.1 parts of silica aerogel, 0.25 parts of flame retardant and 5.0 parts of ceramic particles; Step S2: the high molecular weight polyethylene raw material, talcum powder, monoglyceride, antistatic agent, anti-shrinkage agent, silica aerogel and flame retardant in step S1 are put into a mixer, and then fully mixed and dried; Step S3: adding the mixed raw materials into an extruder, heating and melting the raw materials, and adding ceramic particles into the extruder, and fully mixing the ceramic particles with the molten materials; Step S4: injecting a foaming agent into the extruder to cause the raw material to undergo a foaming reaction, thereby obtaining an EPE foam material, which is then transported as the extruder operates; Step S5: The melt-mixed material is transported to the head and die position of the extruder, the molten raw material is extruded, and the raw material is cooled and formed to prepare pearl cotton; Step S6: The extruded EPE is collected by a reeling device, and the EPE material is driven to move to the embossing machine position, and the embossing machine mold is used to press the surface of the EPE material to form anti-slip convex points.

[0028] Embodiment 3 Step S1: weighing raw materials by weight, 105 parts of high molecular weight polyethylene raw material, 1.5 parts of talc, 25 parts of monoglyceride, 0.3 parts of antistatic agent, 0.5 parts of foaming agent, 0.2 parts of anti-shrinkage agent, 0.1 parts of silica aerogel, 0.25 parts of flame retardant and 1.0 parts of ceramic particles; Step S2: the high molecular weight polyethylene raw material, talcum powder, monoglyceride, antistatic agent, anti-shrinkage agent, silica aerogel and flame retardant in step S1 are put into a mixer, and then fully mixed and dried; Step S3: adding the mixed raw materials into an extruder, heating and melting the raw materials, and adding ceramic particles into the extruder, and fully mixing the ceramic particles with the molten materials; Step S4: injecting a foaming agent into the extruder to cause the raw material to undergo a foaming reaction, thereby obtaining an EPE foam material, which is then transported as the extruder operates; Step S5: The melt-mixed material is transported to the head and die position of the extruder, the molten raw material is extruded, and the raw material is cooled and formed to prepare pearl cotton; Step S6: The extruded EPE is collected by a reeling device, and the EPE material is driven to move to the embossing machine position, and the embossing machine mold is used to press the surface of the EPE material to form anti-slip convex points.

[0029] By adding an equal proportion of ceramic particles to the raw materials for EPE pearl cotton production, the raw materials are heated and melted, so that the ceramic particles are mixed with the molten raw materials, and the ceramic particles and the raw materials are evenly distributed. After the pearl cotton is cooled and shaped, the ceramic particles are distributed on the surface of the pearl cotton, thereby increasing the friction coefficient of the pearl cotton surface, and using an embossing machine mold to press the surface of the pearl cotton material to form anti-slip convex points, which are evenly distributed on the surface of the pearl cotton, thereby increasing the friction resistance of the pearl cotton surface and improving the anti-slip performance of the pearl cotton.

[0030] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An EPE pearl cotton anti-slip process, characterized in that: The following steps are involved: Step S1: weighing raw materials by weight, 95-120 parts of high molecular weight polyethylene raw materials, 1.1-1.8 parts of talc, 18-25 parts of monoglyceride, 0.3-0.5 parts of antistatic agent, 0.3-0.5 parts of foaming agent, 0.1-0.2 parts of anti-shrinkage agent, 0.1-0.2 parts of silica aerogel, 0.2-0.3 parts of flame retardant and 2.1-5.5 parts of ceramic particles; Step S2: adding the high molecular weight polyethylene raw material, talcum powder, monoglyceride, antistatic agent, anti-shrinkage agent, silica aerogel and flame retardant in step S1 into a mixer, and fully mixing and drying them; Step S3: adding the mixed raw materials into an extruder, heating and melting the raw materials, and adding ceramic particles into the extruder, and fully mixing the ceramic particles with the molten materials; Step S4: injecting a foaming agent into the extruder to cause the raw material to undergo a foaming reaction, thereby obtaining an EPE foam material, which is then transported as the extruder operates; Step S5: The melt-mixed material is transported to the head and die position of the extruder, the molten raw material is extruded, and the raw material is cooled and formed to prepare pearl cotton; Step S6: The extruded EPE is collected by a reeling device, and the EPE material is driven to move to the embossing machine position, and the embossing machine mold is used to press the surface of the EPE material to form anti-slip convex points.

2. The EPE pearl cotton anti-slip process according to claim 1, characterized in that: The foaming agent is made of azodicarbonamide material, the antistatic agent is one of sulfuric acid derivatives, phosphoric acid derivatives, amines, quaternary ammonium salts, imidazoles and ethylene oxide derivatives, and the anti-shrinkage agent is a low molecular weight polymer.

3. The EPE pearl cotton anti-slip process according to claim 1, characterized in that: The flame retardant is one of a bromine flame retardant, a phosphorus flame retardant and a nitrogen flame retardant, and the ceramic particles are one of alumina, silicate and carbonate.

4. The EPE pearl cotton anti-slip process according to claim 1, characterized in that: The stirring time of the raw materials in step S2 is 0.5-1h, the stirring temperature is 40-60°C, and the heating temperature of the extruder in step S3 is 180-230°C.

5. The EPE pearl cotton anti-slip process according to claim 1, characterized in that: In the step S4, the foaming agent injection pressure in the extruder is 0-15Mpa, and in the step S6, the hot pressing temperature of the embossing machine is 80-100°C, and the hot pressing time is 5-8s.

6. The EPE pearl cotton anti-slip process according to claim 1, characterized in that: In the step S4, during the heating process, butane in the butane gas tank is injected into the extruder by using a butane gas pump, so that the liquid mixture is foamed into a microporous structure raw material by the effect of butane.

7. The EPE pearl cotton anti-slip process according to claim 1, characterized in that: In step S2, an antistatic agent is added to reduce the surface resistance of the pearl cotton material from 1014-10160 to 108-1010Q, and the antistatic coefficient of the pearl cotton is 109-10110.

8. The EPE pearl cotton anti-slip process according to claim 1, characterized in that: In the step S5, the cooling and shaping treatment is carried out by the cold air equipment, and then the shaped material is pre-pressed by the flattening equipment. After the pre-pressing treatment, the flattening equipment is used for flattening treatment again, and then the flattened and shaped material is wound up by the winding machine to obtain the coiled EPE pearl cotton.

9. The EPE pearl cotton anti-slip process according to claim 1, characterized in that: The silica aerogel in step S1 is obtained by grinding aerogel blocks. The silica aerogel has a large specific surface area and a high porosity, and is used to thicken, thixotropically and reinforce the molten raw materials.